Southeast Asia and the rising China : balancing or bandwagoning? - Nguyen, Phu Tan Huong. (2008)
The post-Cold War debate among realists, liberals and constructivists over East Asian security has not been diminished. Some scholars believe in two dominant theories of realism and liberalism while the others (such as Nikolas Busse) try to prove his assumption of constructivism versus realism. In this thesis, I will argue that all the three lenses can explain for Southeast Asia's strategy towards the rising China, however, realism and constructivism are more effective. Realism can best explain for ASEAN strategies of bandwagoning and hedging with the US against the rising China or with China while engagement belongs to constructivism.